Pharmacodynamic Effects of Vorapaxar in Prior Myocardial Infarction Patients Treated With Potent Oral P2Y12 Receptor Inhibitors With and Without Aspirin: Results of the VORA‐PRATIC Study. Issue 8 (21st April 2020) - Franchi, Francesco; Rollini, Fabiana; Faz, Gabriel; Rivas, Jose Ramon; Rivas, Andrea; Agarwal, Malhar; Briceno, Maryuri; Wali, Mustafa; Nawaz, Ahmed; Silva, Gabriel; Shaikh, Zubair; Maaliki, Naji; et al.
Abstract : Background: Vorapaxar as an adjunct to dual antiplatelet therapy (DAPT) reduces thrombotic events in patients with prior myocardial infarction at the expense of increased bleeding. Withdrawal of aspirin has emerged as a bleeding reduction strategy. The pharmacodynamic effects of vorapaxar with potent P2Y12 inhibitors as well as the impact of dropping aspirin is unexplored and represented the aim of the VORA‐PRATIC (Vorapaxar Therapy in Patients With Prior Myocardial Infarction Treated With Newer Generation P2Y12 Receptor Inhibitors Prasugrel and Ticagrelor) study. Methods and Results: Post–myocardial infarction patients (n=130) on standard DAPT (aspirin+prasugrel or ticagrelor) were randomized to 1 of 3 arms: (1) triple therapy: aspirin+prasugrel/ticagrelor+vorapaxar; (2) dual therapy (drop aspirin): prasugrel/ticagrelor+vorapaxar; (3) DAPT: aspirin+prasugrel/ticagrelor. Pharmacodynamic assessments were performed at 3 time points (baseline and 7 and 30 days). Vorapaxar reduced CAT (collagen‐ADP‐TRAP)–induced platelet aggregation, a marker of platelet‐mediated global thrombogenicity (triple therapy versus DAPT at 30 days: mean difference=–27; 95% CI, –35 to –19; P <0.001; primary end point). This effect was attenuated but still significant in the absence of aspirin (dual therapy versus DAPT at 30 days: mean difference=–15; 95% CI, –23 to –7; P <0.001; between‐group comparisons, P <0.05). Vorapaxar abolished TRAP–induced aggregation ( P <0.001), without affecting thrombin generation and clot strength. There were no differences in markers of P2Y12 reactivity. Markers sensitive to aspirin‐induced effects increased ( P <0.001) in the dual‐therapy arm. Conclusions: In post–myocardial infarction patients treated with potent P2Y12 inhibitors, vorapaxar reduces platelet‐driven global thrombogenicity, an effect that persisted, albeit attenuated, in the absence of aspirin and without affecting markers of P2Y12 reactivity or clot kinetics. The clinical implications of these PD observations warrant future investigation. Registration: URL: https://www.clini​caltr​ials.gov . Unique identifier: NCT02545933.